Ions in liquid crystals doped with nanoparticles: conventional and counterintuitive temperature effects. Issue 9 (15th July 2017) - Garbovskiy, Yuriy
ABSTRACT: The concentration of ions in liquid crystals with fully ionised ionic contaminants does not depend on the temperature. Nanoparticles dispersed in the same liquid crystals change the number of mobile ions through the temperature-dependent adsorption/desorption process. As a result, the concentration of ions in liquid crystal nanocolloids is a strong function of their temperature. This type of temperature dependence is governed by the values of the adsorption activation energy and desorption activation energy. A commonly observed scenario is an increase in the concentration of mobile ions in liquid crystal nanocolloids as their temperature goes up. In this article, an opposite effect is modelled. Under certain conditions, the concentration of ions in liquid crystal nanocolloids decreases with increasing temperature. This unusual behaviour is analysed considering liquid crystals doped with both 100% pure and contaminated nanoparticles. GRAPHICAL ABSTRACT: